2020
DOI: 10.3390/polym12081730
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin Electrolyte Membranes with PFSA-Vinylon Intermediate Layers for PEM Fuel Cells

Abstract: We prepared ultrathin PFSA/PFSA-vinylon/PFSA laminated electrolyte membranes (thickness = 10 μm) for fuel cells without using a reinforcing material. Nafion and Aquivion solutions were used as PFSA polymers. Vinylon was synthesized by formalizing polyvinyl alcohol. From the current-voltage measurements using ultrathin PFSA/PFSA-vinylon/PFSA membranes; the cell resistances are significantly lower than that using a 50 μm Nafion membrane. A high current density was obtained under both low- and high-humidity condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Existing studies have demonstrated that altering the compound composition of the catalyst ink [5][6][7] or the thickness of the membrane [8][9][10] can potentially enhance the fuel cell's efficiency. The ORR's reaction kinetics are significantly faster in alkaline than acidic environments, prompting recent research interest in these conditions.…”
Section: Hor Anodementioning
confidence: 99%
“…Existing studies have demonstrated that altering the compound composition of the catalyst ink [5][6][7] or the thickness of the membrane [8][9][10] can potentially enhance the fuel cell's efficiency. The ORR's reaction kinetics are significantly faster in alkaline than acidic environments, prompting recent research interest in these conditions.…”
Section: Hor Anodementioning
confidence: 99%
“…The other approach generally accepted in the related art applied for comparison of performances is to fix the voltage at 0.65 V, which corresponds to 50% electrical efficiency [72]. In terms of the relative order of performance between membranes, the two approaches generally do not lead to a difference [73,74].…”
Section: Membrane Conductivity and In Situ Single Cell Testingmentioning
confidence: 99%
“…Improved interfacial bonding between polar PVA and Nafion ionomer helped in overcoming the creep deformation observed in case of Nafion/PTFE membrane 65 . Recently, Kim et al 38,39 demonstrated a concept of multilayer membrane preparation (without the use of reinforcing support), using PVA and Nafion. For this purpose, they applied sequential coating layers of PFSA, PFSA‐PVA and PFSA solution on a polyimide sheet.…”
Section: Pva‐based Membranes For Fuel Cellsmentioning
confidence: 99%